Concentration time values in two-arm snatch weightlifting, 109-kg junior class (under 20) - Muraretu, D. C.; Petre, R.-L.; Muraretu, Da.; Teodoru, M. D. (Physical Education, Sport and Kinetotherapy Journal, 2021)
Elite sport is a social phenomenon strongly anchored in the reality of today's world. In an increasingly advanced technological society, no one is surprised by the use of the fastest means of multimedia communication. Implementing this technology in the field of top-level sport offers multiple possibilities for an objective behavioural analysis of athletes during competition. This study, the first to address juniors aged 17-20 years, is part of a broader research aimed at investigating athletes (of both genders and different classes) with regard to certain moments that involve the analysis of concentration times characterising weightlifting styles. The current study focuses on the recording and analysis of concentration times from the moment the feet are just under the bar until the bar is lifted off. Objectives: 1. To examine the possibilities of using the computerised imaging technique in snatch weightlifting; 2. To identify concentration times in snatch weightlifting by recordings and measurements performed with AviSynth equipment. The main research method used is computerised technology connected to video technology. The research presents the recording and analysis of concentration times for snatch weightlifters in value group A, 109-kg Junior Class. It includes 11 male athletes aged 17-20 from various countries. Thus, Bulgaria participated with two athletes, and Albania, Armenia, Azerbaijan, Belarus, Georgia, Poland, Russia, Spain and Turkey, with one athlete each. The result analysis highlights aspects regarding concentration times in the snatch event: average concentration times for the three attempts and for each attempt, the relationship between lifted weight and concentration time.